1996
DOI: 10.1046/j.1365-2125.1996.40110.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of fluconazole and ketoconazole on the metabolism of sulphamethoxazole

Abstract: 1 Cytochrome P450-mediated bioactivation of sulphamethoxazole to a hydroxylamine has been implicated in the hypersensitivity reactions associated with co-trimoxazole administration. Inhibiting the formation of the hydroxylamine may be one method of preventing the high frequency of toxicity which is observed in HIV-infected patients. Therefore, in this study, we have investigated the ability of fluconazole and ketoconazole, known cytochrome P450 inhibitors, to inhibit the formation of sulphamethoxazole hydroxyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
25
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 5 publications
2
25
0
Order By: Relevance
“…CYP2C9 and MPO, consistent with previous literature (10,11,62), but also CYP2C8, were found to be capable of SMX-NHOH generation (Table I). All other enzymes studied were inactive.…”
Section: Discussionsupporting
confidence: 81%
“…CYP2C9 and MPO, consistent with previous literature (10,11,62), but also CYP2C8, were found to be capable of SMX-NHOH generation (Table I). All other enzymes studied were inactive.…”
Section: Discussionsupporting
confidence: 81%
“…Although it was claimed that cyclooxygenase could also N-hydroxylate SMX, a recent study found that the oxidation of SMX in cyclooxygenase incubations containing ascorbate was due to H 2 O 2 in the reaction mixture (Vyas et al, 2006). It is noteworthy that, in the context of the present observations, accurate quantification of a hydroxylamine in vitro (Cribb and Spielberg, 1990a) and in vivo (Gill et al, 1996;Winter et al, 2004) requires the loss of analyte through autoxidation to be blocked with a reducing agent; ascorbate being the agent of choice. In addition, identification of the hydroxylamine has often depended upon cochromatography with an authentic standard using relatively simple high-performance liquid chromatography (HPLC) conditions.…”
mentioning
confidence: 69%
“…This is believed to be an idiosyncratic consequence of enzymatic generation of the hydroxylamine metabolite (SMX hydroxylamine; SMX-NHOH) and subsequent autoxidation to a protein-reactive nitroso species (Cribb et al, 1991). The cellular distribution (Naisbitt et al, 1999), cytotoxicity (Vyas et al, 2005;Lavergne et al, 2006), and immunogenicity (Naisbitt et al, 2001) of SMX metabolites have been studied extensively.SMX-NHOH formation has been found both in hepatic microsomes (Cribb and Spielberg, 1990a;Cribb et al, 1995) and in vivo (Cribb and Spielberg, 1992;Gill et al, 1996). Metabolism of SMX to SMX-NHOH is catalyzed by human hepatic CYP2C9 (Cribb et al, 1995;Gill et al, 1999) and neutrophilic myeloperoxidase (Cribb et al, 1990).…”
mentioning
confidence: 99%
See 2 more Smart Citations